Altered Static and Dynamic Functional Connectivity of Habenula Associated With Suicidal Ideation in First-Episode, Drug-Naïve Patients With Major Depressive Disorder - Qiao, Dan; Zhang, Aixia; Sun, Ning; Yang, Chunxia; Li, Jianying; Zhao, Ting; Wang, Yuchen; Xu, Yifan; Wen, Yujiao; Zhang, Kerang; Liu, Zhifen (Frontiers in Psychiatry, 2020)
Investigating the neurobiological mechanism of suicidal ideation (SI) in major depressive disorder (MDD) may be beneficial to prevent the suicidal behavior. Mounting evidence showed that habenula contributed to the etiology of MDD. The habenula is a key brain region that links forebrain to midbrain, crucial for the processing of reward and aversion. The aim of the present study was to identify whether first-episode, drug-naïve MDD patients with SI displayed altered habenula neural circuitry. 43 and 38 drug-naïve patients with first-episode MDD with or without SI (SI+/- group), as well as 35 healthy control subjects (HC) underwent resting-state functional magnetic resonance imaging. The whole-brain habenula static (sFC) and dynamic functional connectivity (dFC) were calculated to identify regions showing significant difference among these three groups followed by region of interest to region of interest post hoc analysis. For sFC, compared with SI- and HC groups, SI+ group showed decreased sFC from habenula to the precuneus, and the inferior frontal gyrus. Patients with MDD displayed increased sFC from habenula to the putamen but decreased sFC to the precentral gyrus. For dFC, SI+ group showed increased dFC from habenula to the superior temporal gyrus, the precuneus but decreased dFC to the the lingual gyrus, the postcentral gyrus when comparing with SI- and HC groups. Patients with MDD, regardless of SI, displayed decreased dFC from habenula to the angular gyrus. These findings provide evidence that SI in first-episode, drug-naïve patients with MDD may be related to an abnormality in habenula neural circuitry, which may provide the therotical basis of novel treatments.